DEEP LEARNING PADA PEMBELAJARAN SEKOLAH DASAR: UPAYA UNTUK MEMPROMOSIKAN KEMAMPUAN BERPIKIR KRITIS - Yulita Yulita; Mawardi Mawardi; Sabinus Rainer N Christi; Ady Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of deep learning pedagogy in elementary education. A quasi-experimental design with a mixed-methods approach was employed. The experimental group, consisting of 32 students, received instruction through a deep learning-based discovery learning model, while the control group, comprising 30 students, participated in problem-based learning. Data were collected through pre- and post-tests assessing critical thinking skills, classroom observations, and semi-structured interviews with teachers and students. Quantitative data were analyzed using a t-test, whereas qualitative data were thematically analyzed to explore students’ learning experiences and teachers’ reflections. The independent sample t-test comparing post-test scores between groups yielded a p-value of 0.013, indicating a significant difference in mathematical critical thinking skills between the experimental and control groups at the α = 0.05 significance level. The findings reveal that students in the experimental group demonstrated significantly higher critical thinking abilities than those in the control group. The integration of learning trajectories and learning obstacle analysis helped teachers anticipate potential learning barriers and provide appropriate scaffolding. Qualitative evidence also showed that students became more active, reflective, and collaborative when engaging with complex tasks. Overall, this study underscores the potential of deep learning pedagogy in fostering critical thinking skills in elementary education.